1967
DOI: 10.1071/zo9670941
|View full text |Cite
|
Sign up to set email alerts
|

The structure of the Spiracles of the cattle tick, Boophilus microplus

Abstract: The structures of the nymphal and adult spiracles of the tick, Boophilus microplus, have been examined by means of serial sections and a stereoscan electron microscope. Contrary to the views of recent writers, the functional openings of the spiracle have been found to be holes or aeropyles in the peripheral part of the spiracular plate of the adult tick. The ostium of previous writers is shown to be the ecdysial tube, which is present only in the spiracles of adult ixodid ticks. After the nymphal-adult ecdysis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

1971
1971
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 0 publications
1
14
0
Order By: Relevance
“…The gross morphology is in agreement with available descriptions of this and other ixodid species (Pugh et al, 1988;Pugh, 1997): the connection between the labyrinth, the sub-ostial space and the tracheal atrium is clearly visible. Moreover, we confirmed connections between the chambers by fenestrations, the closed condition of the "ostium" (Hinton, 1967; Pugh, 1997;Woolley, 1972) and the cuticular channels through the baseplate. The pedicels in I. ricinus have more than three edges, a condition typical for Ixodinae (Pugh, 1997).…”
Section: Discussionsupporting
confidence: 49%
See 1 more Smart Citation
“…The gross morphology is in agreement with available descriptions of this and other ixodid species (Pugh et al, 1988;Pugh, 1997): the connection between the labyrinth, the sub-ostial space and the tracheal atrium is clearly visible. Moreover, we confirmed connections between the chambers by fenestrations, the closed condition of the "ostium" (Hinton, 1967; Pugh, 1997;Woolley, 1972) and the cuticular channels through the baseplate. The pedicels in I. ricinus have more than three edges, a condition typical for Ixodinae (Pugh, 1997).…”
Section: Discussionsupporting
confidence: 49%
“…In previous descriptions they were interpreted as sensory structures (Nordenskiöld, 1906;Roshdy and Hefnawy, 1973), as "Krobylophoren", organs of sensory and glandular function (Schulze, 1942), or as integumental glands (Arthur, 1956). Scanning and transmission electron microscopy (SEM and TEM) studies revealed more details on spiracle morphology (Hinton, 1967;Woolley, 1972) and supported a glandular nature of the cytoplasmic extensions (Baker, 1997;Sixl and Sixl-Voigt, 1974;Walker et al, 1996). Nevertheless, there are morphological differences in the spiracle glands of the species studied, and their function remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…In argasid ticks, the spiracular plate lacks pore-like chambers and goblets, and has a simple opening set in a hinged flap (Fig. 4) which passes directly into an atrial cavity (Hinton 1967).…”
Section: General Natural Historymentioning
confidence: 99%
“…Hinton [19] described the size and form of the aeropyles or spiracles of Boophilus. This author stated that the main function of the aeropyles is to block entry of water under field conditions.…”
Section: Discussionmentioning
confidence: 99%